Morphogenetic Plasticity of Neuronal Elements in Cerebellar Glomeruli during Deafferentation-Induced Synaptic Reorganization. (1997) - Hámori, József; Jakab, Robert L.; Takács, József
Abstract : Reorganization of the cerebellar glomerulus, the main synaptic complex within the granule cell layer, was investigated using quantitative morphological techniques. All afferents to the cerebellar cortex, including mossy-fibers, were surgically destroyed by undercutting the cerebellar vermis. Fifteen days after the operation, which resulted in the removal of the main excitatory afferent to the glomerulus, a significant reorganization of the whole synaptic complex was observed, whereas the structural integrity of the glomerulus was remarkably well preserved. This was indicated by the observation that the number of granule cell dendrites (≈50 per glomerulus), as well as the number of dendritic digits (≈210 per glomerulus) bearing most of the ≈230 synaptic junctions per glomerulus, did not change significantly after mossy-fiber degeneration. The total number of synapses in the reorganized glomerulus did not change either, despite the disappearance of two-thirds of (excitatory) synaptic junctions caused by mossy-fiber degeneration. In the reorganized glomeruli, however, the inhibitory, GABA-containing Golgi axonal varicosities became the dominant synaptic type—about four-fifths (≈200) of all synapses within the glomerulus—whereas the dendritic synapses between the granule cells represented only one-fifth of all synaptic junctions. The quantitative data of the reorganized cerebellar glomerulus demonstrate both a remarkable constancy and a plasticity of he excitatory granule cells and inhibitory Golgi neurons building up this synaptic complex. constancy (the preservation of certain specific structural features) is represented by an eventually unchanged number of dendrites and synaptic junctions within the deafferented lomerulus. Such constancy was made possible, however, by the morphogenetic plasticity of both nerve-cell types to produce new, dendrodendritic and axo-dendritic synapses to compensate for the loss of mossy-fiber synapses.